Nutritional status assessment of children aged 0-5 years and its determinants in a tribal community of Coimbatore district - Senthilkumar, S. K.; Chacko, Thomas V.; Suvetha, K. (International Journal Of Community Medicine And Public Health, 2018)
Background: Nutritional assessment in children is very important to prevent nutritional disorders and to decrease the morbidity and mortality. The present study was undertaken to assess the prevalence and determinants of malnutrition among children aged 0-5 years in a tribal community of Coimbatore district. Anaikatty and Palamalai tribal areas of Perianaikenpalayam block (population=347062) was selected for our study. Methods: A total of 206 children aged 0-5 years were included in the study after implementing the exclusion criteria. Results: Overall prevalence of malnutrition found to be 51%. These 51% (105) malnourished children consisted of 41.3% underweight, of which 11.2% were severely underweight. Prevalence of stunting was 32.5%, of which 6.3% were severely stunted. About 21.8% children were wasted and 6.8% were severely wasted among them. Socio-demographic factors like total number of family members exceeding four, mother’s educational status, father’s educational status, mother’s occupational status, socio-economic status, alcohol usage by any family member, and mother’s nutritional status were found to be significantly associated with malnutrition on univariate analysis. Conclusions: The problems of low standard of living, hunger, starvation, malnutrition, agricultural illiteracy, poor antenatal care, disease, poor sanitary and housing facilities, etc. has to be improved totally by implementation of policy that already exists.